Molecular cloning of an erythromycin resistance determinant in streptococci. - Behnke, D (1980)
The erythromycin resistance determinant of plasmid pDB102, a derivative of plasmid pSM19035, was cloned into the single HindIII site of the 3.6-megadalton cryptic Streptococcus mutans plasmid pVA318 and introduced into Streptococcus sanguis strain Challis by transformation. Plasmid pDB201, which was isolated from one of the transformants, consisted of the vector plasmid and the 1.15-megadalton HindIII fragment D of pSM19035. HindIII fragment D contained within it one of the two unique "spacer" sequences of pSM19035. Electron micrographs of self-annealed molecules of the recombinant plasmid revealed classical stem-loop structures, and the resistance determinant of pSM19035 appeared as a transposon-like structure. No differences were observed in either the type or the level of erythromycin resistance by pSM19035 or pDB201. The availability of a cloned erythromycin resistance determinant should be useful for future comparative studies of macrolide, lincosamide, and streptogramin B resistance plasmids in streptococci.